On the number of symbols that forces a transversal. (21st March 2020) - Keevash, Peter; Yepremyan, Liana
Abstract: Akbari and Alipour [1] conjectured that any Latin array of order n with at least n 2 /2 symbols contains a transversal. For large n, we confirm this conjecture, and moreover, we show that n 399/200 symbols suffice.